A formação de professores e a ludicidade como aspecto teórico-metodológico para o ensino e aprendizagem em ciências - SILVA, Kamili Souza da (2020)
The present work has as main objective to analyze playful proposals in science teaching in the early years of elementary school, more specifically about how we can evaluate the learning of children in this stage of schooling making use of dynamic class through playfulness, and differentiated in the treatment of children. contents of science in this phase of teaching, as well as to analyze the historical aspects of Science Teacher Training in Brazil and the way science education was and is being treated within Brazilian schools. Based on this thinking, it was also necessary to analyze the relationship between playfulness from the perspective of teaching and learning and its insertion within schools, as a feasible alternative and as a viable instrument for teaching. The formation of science teachers has suffered numerous external influences since the 1950s, being closely linked to scientific and technological development as alternatives for the growth and advancement of the country, from the perspective of accompanying the great world economic powers, being mainly guided by the US models of doing science. This article will discuss historical and didactic aspects that guide the educational proposals of science teaching over the years, as well as ratify the importance of technological development in this evolutionary process, without delaying the relationships between scientific and technological knowledge and their contributions. and correlations with society and its evolution. In an analysis of the development process of the country through the implementation of public policies for the valorization of science and technology in Brazil, they provide an understanding of how important and necessary it is to invest in an education considering the criteria of a qualitative approach to the teaching of science. Science that is intended for children in the early years of elementary school, so that this teaching is not passive, informative or neutral. To guide this study, I asked myself the following questions: How was science teaching treated in the history of Brazilian education, based on the country's scientific and technological development since the 1950s? ; How was the formation of science teachers treated in Brazil? ; What do scholars say about playfulness in teaching school content? This study had as methodology of presentation of results, a qualitative bibliographical research, where the intention was to show the relevant aspects of the educational process of the Brazilian schools.